RANCANG BANGUN PELAYANAN TERPADU SATU PINTU (PTSP) PADA MAN 1 MAGELANG - achiriyana, ita; Febriani, Yeza; Handayani, Riska Dwi; Kanafi, Kanafi (STMIK BINA PATRIA, 2024)
The era of globalization brings significant changes in various aspects of life, including in the world of education. MAN 1 Magelang is one of the educational institutions that strives to utilize technology to improve services provided through the website One-Stop Integrated Service (PTSP). With the existence of the PTSP website, it is expected to facilitate the management of services for schools, and also provide convenience to the community who need services from MAN 1 Magelang because they do not have to come to the school when submitting a service request. The purpose of this study is to design and build a website-based information system that suits the needs of MAN 1 Magelang, with a focus on efficiency and reliability to support PTSP, and to see its impact on service quality. This research is a software development research with the agile method which is an advanced approach to SDLC (System Development Life Cycle). The research procedures carried out consist of planning, design, development, testing, implementation, review, and launch. User evaluation testing or user acceptance testing (UAT) produced a value of 90%. This shows that Admin and Guest users stated that they